Open fractures of the proximal humerus treated with the Ilizarov method -: 12 patients followed 3-8 years - Karatosun, V; Alekberov, C; Baran, Ö; Serin, E; Alici, E; Balci, C (Taylor & Francis as, 2002)
We followed 12 patients who had been treated with the Ilizarov method for open proximal humeral fractures for more than 3 years. No wound infection occurred. Avascular necrosis and nonunion were each detected in 1 patient. According to Neer's criteria, the outcome was excellent or satisfactory in 8 patients.